Effect of oxygen giving with frequency of Fetal Heart Rate (DJJ) on inpartu fetal distress patients at Panti Nugroho Hospital, Purbalingga - Muhammad Galih Widyanto; Rahmaya Nova Handayani; Dwi Novitasari (Riset Informasi Kesehatan, 2023)
ABSTRACT Background: Fetal distress is one of the causes of fetal death in the world, according to the World Health Organization (WHO) in 2015, data for the last 5 years amounted to 637,000 deaths caused by fetal distress. The incidence in Indonesia is that 34.7% of 100,000 live births experience fetal distress. Fetal distress is an emergency case of pregnancy in the fetus. Fetal distresss causes fetal hypoxia so that the fetus requires immediate oxygen supply. Objective: to determine the characteristics of the respondents, fetal heart rate before and after administration of oxygen, the effect of giving oxygen to in-partum patients with fetal distress at Panti Nugroho Hospital, Purbalingga. Method: using a pre-experimental design type of one group pretest posttest. The research sample was pregnant women in childbirth with fetal distress by accidental sampling technique, namely 30 respondents. Observation sheet containing mother's identity, mother's pregnancy status, gestational age and FHR value before and after administration of oxygen. Data analysis used bivariate analysis, namely the Wilcoxon test. Results: 20% showed an improvement in fetal heart rate of 10-20 beats/minute, 46% had an improvement in fetal heart rate of 20-30 beats/minute, while 33.3% had an improvement in fetal heart rate of more than 30 beats/minute. There is an effect of giving 4 liters/minute of oxygen to inpartu patients with fetal distress with a p value of 0.00 (p>0.05). Conclusion: Administration of nasal cannula oxygen 4 liters/minute can affect the fetal heart rate. Key words: labor, administration of oxygen, fetal distress